Effect of Annealing Process on CH3NH3PbI3-XClX Film Morphology of Planar Heterojunction Perovskite Solar Cells with Optimal Compact TiO2 Layer - Dan Chen; Xiaoping Zou; Hong Yang; Ningning Zhang; Wenbin Jin; Xiao Bai; Ying Yang (International Journal of Photoenergy)
The morphology of compact TiO2 film used as an electron-selective layer and perovskite film used as a light absorption layer in planar perovskite solar cells has a significant influence on the photovoltaic performance of the devices. In this paper, the spin coating speed of the compact TiO2 is investigated in order to get a high-quality film and the compact TiO2 film exhibits pinhole- and crack-free films treated by 2000 rpm for 60 s. Furthermore, the effect of annealing process, including annealing temperature and annealing program, on CH3NH3PbI3-XClX film morphology is studied. At the optimal annealing temperature of 100°C, the CH3NH3PbI3-XClX morphology fabricated by multistep slow annealing method has smaller grain boundaries and holes than that prepared by one-step direct annealing method, which results in the reduction of grain boundary recombination and the increase of Voc. With all optimal procedures, a planar fluorine-doped tin oxide (FTO) substrate/compact TiO2/CH3NH3PbI3-XClX/Spiro-MeOTAD/Au cell is prepared for an active area of 0.1 cm2. It has achieved a power conversion efficiency (PCE) of 14.64%, which is 80.3% higher than the reference cell (8.12% PCE) without optimal perovskite layer. We anticipate that the annealing process with optimal compact TiO2 layer would possibly become a promising method for future industrialization of planar perovskite solar cells.